Pengaruh Pelatihan, Komunikasi dan Kepuasan Kerja Terhadap Kinerja Pegawai Dinas Sosial - Dina Lorenza; Suhaila Husna Samosir; Horia Siregar; Emelia Rahmadany Putri Gami; Ova Novi Irama (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The purpose of this study was to find out and analyze the effect of job training, job communication and job satisfaction on employee performance in the Social Service Office of Serdang Bedagai Regency. This type of research is quantitative. The population in this study were all employees at the Serdang Bedagai District Social Service, totaling 58 people. In research sampling using saturated samples. Then this sampling is based on the total population, namely 58 people with a saturated sample/sampling quota. Data collection techniques in this study by observation, questionnaires and questionnaires with data measurement scale Likert scale. Data analysis techniques using validity, reliability and classical assumptions. Methods of data analysis using multiple linear regression with the help of the SPSS program. The results of the t test show that job training has a positive and significant effect on employee performance. Work communication has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. The results of the F test show that job training, job communication and job satisfaction simultaneously affect employee performance at the Serdang Bedagai District Social Service with Fcount (39.948) > Ftable (2.77), and a significance value of 0.000 <0.05. The adjusted coefficient of determination (R Square) is 0.689, this means that 68.9% of the dependent variable can be explained by the independent variables while the rest (100% - 68.9% = 21.1%) is explained by other variables outside the variables explained.